Religion and the challenges of science - Sweet, William; Feist, Richard, 1964- (Ashgate Pub., 2007)
Does science pose a challenge to religion and religious belief? This volume provides background to the current 'science and religion' debate, yet focuses as well on themes where recent discussion of the relation between science and religion has been particularly concentrated.